PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA SMPN 10 PALOPO - Nurhapni Joring; Nur Saqinah Galugu; Ainul Fahmi (IKIP Siliwangi, 2026)
This study aims to examine the effect of group counseling services using the role playing technique on improving students' learning motivation at SMPN 10 Palopo. A quantitative approach was applied with a quasi-experimental method, specifically a pretest-posttest design without a control group. The sample consisted of 15 eighth-grade students with low learning motivation, selected by purposive sampling. Data were collected using a learning motivation scale and analyzed using Paired Sample t-Test with SPSS. The results showed a significant increase in learning motivation after the intervention, with a pre-test average of 69.2 and a post-test average of 81, and a significance value of 0.000 (p < 0.05). Thus, the role playing technique is effective in enhancing students' learning motivation.